THE ACCURACY OF STUDENTS TRANSLATION OF REPORT TEXT IN THE ENGLISH LANGUAGE STUDY PROGRAM OF KHAIRUN UNIVERSITY - Rahmatia, Rahmatia; Ali, Silvani Umar; Jasin, Hamida; Adam, Samsudin Hi. (Jurnal Bilingual, 2023)
The purpose of this research was to find out students' translation accuracy of report text in an English education study program. This research used a descriptive qualitative method with the third-semester students as the respondents of this research. The main data source was taken from The Jakarta Post, Bicara Melalui Kain": Redefining textile narratives in Indonesia. The technique of data collection used in this research was using one instrument: the results of the student's text translation. In assessing the accuracy of students' translations, the researcher used Nababan's (2012) accuracy assessment. The data shows that from 14 respondents from third-semester students, the accuracy of students' translations was still low. The low accuracy of students' translation was caused by the lack of vocabulary where there were many missing words, mistranslations, and distortion of meaning which affected the meaning of the text based on Nababan's (2012) Accuracy assessment. Around 7 out of 14 respondents were eliminated by the researcher caused by the used of Google Translate in transferring the English text (SL) into Indonesian (TL) which does not follow the researcher's provisions in her research. Regarding the result, this research could be a reference for lectures in improving students' translation ability.